2019
DOI: 10.3168/jds.2019-16836
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin administration during the dry period stimulates subsequent milk yield and weight gain of offspring in subtropical does kidding in summer

Abstract: In the present experiment, we tested the hypothesis that in does kidding in summer, melatonin administration during dry period is galactopoietic for the subsequent lactation and results in improved growth of their suckling kids. Twenty-five multiparous pregnant creole does were enrolled into a randomized complete block design during their dry period in the 49 d prepartum, and under natural long photoperiods around the summer solstice, pregnant does either received 2 subcutaneous ear implants (18 mg) of melaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Melatonin production exhibits an apparent circadian rhythm, with the peak at dark and the baseline level during the day [28]. Melatonin administration during a dry period is galactopoietic for the subsequent lactation in goats [29]. Few studies have reported the effects of melatonin supplement on milk quality in cows evaluated by the DHI, which is considered as the best index to reflect milk quality in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin production exhibits an apparent circadian rhythm, with the peak at dark and the baseline level during the day [28]. Melatonin administration during a dry period is galactopoietic for the subsequent lactation in goats [29]. Few studies have reported the effects of melatonin supplement on milk quality in cows evaluated by the DHI, which is considered as the best index to reflect milk quality in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Cashmere goats that had received an implant at day 50 of lactation presented a higher fat content in the milk of than was in the milk of control goats; however, daily yields of milk, milk protein, and milk lactose were lower in the implanted goats than they were in the controls goats [14]. Melatonin administration to does in the dry period, seven weeks before kidding, produced a galactopoietic response in the subsequent lactation and an improved daily weight gain of their suckling kids, especially, males [15].…”
Section: Discussionmentioning
confidence: 89%
“…Yang et al (2019) reported a higher fat content in the milk of Cashmere goats that had received an implant at day 50 of lactation than was in the milk of control goats; however, daily yields of milk, milk protein, and milk lactose were lower in the implanted goats than they were in the controls goats. Melatonin administration to does in the dry period, seven weeks before kidding, produced a galactopoietic response in the subsequent lactation and an improved daily weight gain of their suckling kids, especially, males (Avilés et al 2019).…”
Section: Discussionmentioning
confidence: 97%